INTERNATIONAL BUSINESS STRATEGY FOR ISLAMIC BANKING INDUSTRY IN INDONESIA: AN ANALYSIS FOR EXPANSION - Kusuma, Kumara Adji; Rosyihin, Farih Ayu Mukhoirotin Sirojul Umma; Maharani, Febi Putri; Yulianto, Mochamad Rizal; Wai, Khoong Tai (PT. Antis International Publisher, 2025)
Objective: The Indonesian Islamic banking industry holds tremendous potential for growth, driven by factors like the large Muslim population, government support, increasing economic activity, and growing demand for ethical and Sharia-compliant financial products. In its implementation of course there are challenges, but with the right strategies, Indonesia’s Islamic banking sector could emerge as a leader not only in the Southeast Asian region but also on the global stage. This study will be covering the environments where an Islamic bank would survive, grow and develop itself, including examining on the current situation of the Islamic banking industry in Indonesia: its strength, weakness, opportunities and threats internally and externally. Method: This study uses a qualitative method with primary and secondary data collection. This research approach uses a case study of Indonesian Islamic banks. Results: The result of the analysis will be used to build up a structure, let’s say a methodology, a mechanism or a framework which allows an Islamic bank in Indonesia to mapping out and measure the feasibility of its enterprise in the targeted country as new area of market and create a step by step strategy for the bank to strengthen its basis in the new market. This will help the Indonesian Islamic financial institution especially Islamic banks in opening up the expansion possibilities in a certain country in the world. Novelty: This will help the Indonesian Islamic financial institution especially Islamic banks in opening up the expansion possibilities in a certain country in the world.